Influence of 2′-Fucosyllactose and Bifidobacterium longum Subspecies infantis Supplementation on Cognitive and Structural Brain Development in Young Pigs - Sutkus, Loretta T.; Joung, Sangyun; Hirvonen, Johanna; Jensen, Henrik Max; Ouwehand, Arthur C.; Mukherjea, Ratna; Donovan, Sharon M.; Dilger, Ryan N. (Frontiers in Neuroscience, 2022)
Development of the gut-brain axis during early-life is an important contributor of brain structural and functional development. Human milk oligosaccharides and gut microbiota have potential beneficial effects on various aspects of development; however, the effects of 2′-fucosyllactose (2′-FL) and Bifidobacterium longum subsp. infantis Bi-26 (Bi-26) administration during infancy separately and combined are still not clear. Therefore, we investigated the effects of early administration of dietary 2′-FL and Bi-26 on brain structural and functional development in the young pig. From postnatal day (PND) 2 to 34 or 35, fifty-two intact male pigs were randomly assigned to treatment groups in a 2×2 factorial arrangement and provided ad libitum access to a nutritionally adequate milk replacer without or with 1.0 g of 2′-FL/L of reconstituted liquid. Pigs with each diet group were further stratified to receive a daily oral dose of glycerol stock without or with Bi-26 (109 CFU). Pigs were subjected to the novel object recognition (NOR) task from PND 27 to 31 to assess recognition memory and subsequently underwent magnetic resonance imaging procedures at PND 32 or 33 to assess brain macrostructure and microstructure. Pigs that received Bi-26 had smaller absolute brain volumes for 9 of 27 brain regions of interest, and smaller relative volumes for 2 regions associated with kinesthesia (P < 0.05). Synbiotic administration of 2′-FL and Bi-26 elicited interactive effects (P < 0.05) on several microstructural brain components, where dual supplementation negated the effects of each test article alone. Behavioral outcomes indicated that pigs did not express novelty preference, regardless of treatment group, demonstrating no effects of 2′-FL and Bi-26 on recognition memory when supplemented alone or in combination. Interactive effects (P < 0.05) were observed for the number of all object visits, latency to the first object visit, and number of familiar object visits. Pigs that did not receive Bi-26 supplementation exhibited less time interacting with the familiar object in total (P = 0.002) and on average (P = 0.005). In conclusion, supplementation of 2′-FL and/or Bi-26 elicited some alterations in object exploratory behaviors and macro/micro-structures of the brain, but changes in recognition memory were not observed.